Development of Self-Optimizing Systems - Gausemeier, Jürgen; Korf, Sebastian; Porrmann, Mario; Stahl, Katharina; Sudmann, Oliver; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Driver-in-the-Loop-Simulation - Amelunxen, Hendrik; Berssenbrügge, Jan; Schmid, Christoph (Automobil Elektronik)

Methods for the Domain-Spanning Conceptual Design - Anacker, Harald; Brenner, Christian; Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Sch{\, Wilhelm; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Methods for the Domain-Spanning Conceptual Design - Anacker, Harald; Brenner, Christian; Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Schäfer, Wilhelm; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Geschäftsmodellmuster für disruptive Technologien - Amshoft, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

The development order as the basis for a forward-looking and system-oriented product creation - Wiederkehr, Olga; Dumitrescu, Roman; Gausemeier, J {\ "u} rgen (Systems Engineering Day 2014)

Framework for modeling a plausible system structure of mechatronic systems - Kaiser, Lydia

Challenges - Iwanek, Peter; Meyer, Tobias; Priesterjahn, Claudia; Sextro, Walter; Vaßholz, Mareen (Dependability of Self-optimizing Mechatronic Systems)

Strategic planning of market services in the context of Industry 4.0 - Gausemeier, J {\ "u} rgen; Amshoff, Benjamin; D ü lme, Christian; Kage, Martin (Foresight and Technology Planning)

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network - Gries, Thomas; Dung, Ha Van (Modern Economy)

Untersuchung des Erreichbarkeitsproblems in ungerichteten Graphen bezüglich den Komplexitätsklassen L und SL - Biermeier, Felix

Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Erwerb von Handlungskompetenz in Communities of Practice - Bloh, Thiemo

Zur Bedeutung Anderer bei der Entwicklung von Expertise – Eine Analyse berufsbiographischer Narrationen von Grundschullehrkräften - Bloh, Thiemo

Korrosionsuntersuchungen an experimentellen und technisch relevanten Magnesiumlegierungen - Hoyer, Kay-Peter

Rainbow connection number of graph power and graph products - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Rainbow connection number and radius - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

The setting behavior of dispersion adhesives during bonding of Wood Plastic Composites (WPC) - Moritzer, Elmar; Hopp, Matthias (67th Annual Assembly of the International Institute of Welding (IIW))

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, Michael; Jachura, M.; Brecht, Benjamin; Avenhaus, M.; Silberhorn, Christine (Physical Review A)

Absence of pressure sensitivity of apparent wall slip in pressure-driven flow of non-colloidal suspensions - Pieper, Sven; Kirchhoff, Nadine; Schmid, Hans-Joachim (Rheologica Acta)
We investigated an explanation for the length dependence of apparent wall slip in capillary and slit die experiments that had been implied in earlier studies. Firstly, we used a very long slit die fitted with six equidistant pressure transducers and an adjustable outlet. It was found that, all other parameters being equal, the impact of pressure on the flow behavior of suspensions was not different from the impact on the unfilled matrix fluid. Particle-related properties, such as apparent wall slip, were therefore not influenced by pressure as assumed by other authors. Secondly, we determined wall slip velocities by both the Mooney method and numerical simulation, based on an implementation of Phillips constitutive equation for particle migration. This led to a similar length dependence of wall slip as had been reported in an earlier work. We concluded that this was due to the transient nature of particle migration and its interrelationship with apparent wall slip, rather than an influence of pressure.

Ultrafine Dust Filtration Using Precoat Materials Considering the Influence of Filter Media - Schiller, Sascha; Schmid, Hans-Joachim (Chemical Engineering & Technology)
Ultrafine dust separation from different sources like industry, traffic, or private households has become increasingly important in the last decade. A compact baghouse filter system has been developed which is suitable for pellet heaters. For filtration, a precoat material is required to prevent clogging of the filter media by the ultrafine dust particles. In order to ensure the best performance of this filter system, different combinations of filter media and precoat materials, e.g., grade efficiencies and the cake area load for the various filter media, were investigated in a special test rig. With this highly efficient technology, extremely high separation efficiencies of > 99 % and ultrafine dust concentrations of > 1 mg cm−3 could be reached in a long-term stable process.

Simulation of Capillary Bridges between Nanoscale Particles - Dörmann, Michael; Schmid, Hans-Joachim (Langmuir)
Capillary forces are very important as they exceed in general other adhesion forces. But at the same time the exact calculation of these forces is very complex, so often assumptions and approximations are used. Previous research was done with regard to micrometer sized particles, but the behavior of nanoscale particles is different. Hence, the results for micrometer sized particles cannot be directly transferred when considering nanoscale particles. Therefore, a simulation method was developed to calculate numerically the shape of a rotationally symmetrical capillary bridge between two spherical particles or a particle and a plate. The capillary bridge in the gap between the particles is formed due to capillary condensation and is in thermodynamic equilibrium with the gas phase. Hence the Kelvin equation and the Young–Laplace equation can be used to calculate the profile of the capillary bridge, depending on the relative humidity of the surrounding air. The bridge profile consists of several elements that are determined consecutively and interpolated linearly. After the shape is determined, the volume and force, divided into capillary pressure force and surface tension force, can be calculated. The validation of this numerical model will be shown by comparison with several different analytical calculations for micrometer-sized particles. Furthermore, it is demonstrated that two often used approximations, (1) the toroidal approximation and (2) the use of an effective radius, cannot be used for nanoscale particles without remarkable mistake. It will be discussed how the capillary force and its components depend on different parameters, like particle size, relative humidity, contact angle, and distance, respectively. The rupture of a capillary bridge due to particle separation will also be presented.

Outsourcing von Lagerdienstleistungen als operatives Entscheidungsproblem - Betz, Stefan (Logistikorientiertes Produktionsmanagement)

Verfahren zur Entwicklung geschäftsmodellorientierter Diversifikationsstrategien - Lehner, Markus

Systematik für die integrative Konzipierung der Montage auf Basis der Prinziplösung mechatronischer Systeme - Brandis, Rinje

Systematik zur Entwicklung von Geschäftsmodellen in der Produktentstehung - Köster, Oliver

Rahmenwerk zur Modellierung einer plausiblen Systemstruktur mechatronischer Systeme - Kaiser, Lydia

Systematik zur Planung von CrossIndustry-Innovationen - Echterhoff, Niklas

A Design Framework for Developing a Reconfigurable Driving Simulator - Hassan, Bassem

Model Consistency Management for Systems Engineering - Rieke, Jan

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Systematik der virtuellen Inbetriebnahme von automatisierten Produktionssystemen - Brökelmann, Jan

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Detection of nonlocal superpositions - Gutiérrez-Esparza, A. J.; Pimenta, W. M.; Marques, B.; Matoso, A. A.; Sperling, Jan; Vogel, W.; Pádua, S. (Physical Review A)

Witnessing the degree of nonclassicality of light - Mraz, M.; Sperling, Jan; Vogel, W.; Hage, B. (Physical Review A)